Defining scenarios of future vectors of change in marine life and associated economic sectors. (5th February 2018) - Groeneveld, Rolf A.; Bosello, Francesco; Butenschön, Momme; Elliott, Mike; Peck, Myron A.; Pinnegar, John K.
Abstract: Addressing the multitude of challenges in marine policy requires an integrated approach that considers the multitude of drivers, pressures, and interests, from several disciplinary angles. Scenarios are needed to harmonise the analyses of different components of the marine system, and to deal with the uncertainty and complexity of the societal and biogeophysical dynamics in the system. This study considers a set of socio-economic scenarios to (1) explore possible futures in relation to marine invasive species, outbreak forming species, and gradual changes in species distribution and productivity; and (2) harmonise the projection modelling performed within associated studies. The exercise demonstrates that developing interdisciplinary scenarios as developed in this study is particularly complicated due to (1) the wide variety in endogeneity or exogeneity of variables in the different analyses involved; (2) the dual role of policy decisions as variables in a scenario or decisions to be evaluated and compared to other decisions; and (3) the substantial difference in time scale between societal and physical drivers. Highlights: The complex nature of marine policy requires interdisciplinary scenarios. We present a set of scenarios to facilitate analysis of marine policy. Dual role of policy decisions complicates developing scenarios. Societal and physical drivers differ substantially in time scale.